1995
DOI: 10.1039/c39950000655
|View full text |Cite
|
Sign up to set email alerts
|

Arylalkane oxidation by dioxo[4,4′-di(tert-butyl)-2,2′-bipyridyl]molybdenum(VI) complexes

Abstract: Ary la I ka ne Oxid at io n by D ioxo[ 4,4/-d i ( tert-but y I ) -2,2'-bi pyr idyl] mol ybden u m ( VI) Complexes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…The torsion angles O2-Mo1...Mo2-O5 for (9) and O3-Mo1...Mo2-O5 for (7) are 114.6°and 165.0°, respectively. The lengths and angles are similar to other hexacoordinate dioxo Mo(VI), W(VI) and dioxo-l-oxo Mo(VI), W(VI) complexes containing bipyridine derivates and thiocyanato, halogen ligands [8,9,19,23]. …”
Section: Spectroscopic Characterizationmentioning
confidence: 67%
See 1 more Smart Citation
“…The torsion angles O2-Mo1...Mo2-O5 for (9) and O3-Mo1...Mo2-O5 for (7) are 114.6°and 165.0°, respectively. The lengths and angles are similar to other hexacoordinate dioxo Mo(VI), W(VI) and dioxo-l-oxo Mo(VI), W(VI) complexes containing bipyridine derivates and thiocyanato, halogen ligands [8,9,19,23]. …”
Section: Spectroscopic Characterizationmentioning
confidence: 67%
“…Whereas the l-oxo-bromo-dioxomolybdenum dimer was obtained by an analogous procedure from Na 2 MoO 4 in aqueous HBr and the adequate bipyridine, the monomeric dibromodioxomolybdenum complex was formed directly by reacting MoO 2 Br 2 with 2,2¢-t-butylpyridine in THF [19]. This method avoided the cumbersome involvment of the tetraphenylphosphonium salts.…”
Section: Synthesis Of Complexesmentioning
confidence: 99%
“…Arzoumanian and co-workers found that the tetraphenylphosphonium salt, (PPh 4 ) 2 [Mo VI O 2 (NCS) 4 ] (1), catalysed the model reaction approximately 20 times more efficiently than Mo VI O 2 (S 2 CNEt) 2 [9]. In an attempt to improve the oxidising power of the anion [Mo VI O 2 (NCS) 4 ] 2-, the same group reacted 1 with various bipyridines and obtained, in the case of 4,4 0 -di-tert-butyl-2,2 0 -bipyridine, the neutral monomer Mo VI O 2 (NCS) 2 (di-tBu-bipy) (2) [10,11] with exceptional OAT properties, not only towards phosphines, but also towards arylalkanes and alcohols [12,13]. These oxidation reactions become catalytic in the presence of DMSO.…”
Section: Introductionmentioning
confidence: 98%
“…1). The solid-state structures of the monometallic (I-VI) [9,13,14] and bimetallic (IX-XI) [11,16] complexes show a distorted octahedral geometry around the metal atom, while for the heptacoordinated compounds VII and VIII, the ligands are placed around the molybdenum centre giving a pseudopentagonal bipyramidal geometry. [8,15] The chemical shifts observed cover a wide range (ca 1100 ppm, from +500 to −600 ppm), depending on the electronic density on the metal by modulation of the coordinated ligands (Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An exponential window function was applied with a line broadening of 20-200 Hz before Fourier transform to obtain an optimum signal-to-noise ratio. Ligands 3, [12] (R)-4 and (S)-5, [9] and complexes II, [13] III and XI, [11] IV-V, [9] VI, [14] VII, [15] IX [16] and X [8] were prepared according to published methods. Complexes I [17] and VIII [18] were prepared following the methodology described for related compounds.…”
Section: Methodsmentioning
confidence: 99%